2022
DOI: 10.3390/jcm11237189
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Importance of Corticalization Occurring in Alveolar Bone Surrounding a Dental Implant

Abstract: Several measures describing the transformation of trabecular bone to cortical bone on the basis of analysis of intraoral radiographs are known (including bone index or corticalization index, CI). At the same time, it has been noted that after functional loading of dental implants such transformations occur in the bone directly adjacent to the fixture. Intuitively, it seems that this is a process conducive to the long-term maintenance of dental implants and certainly necessary when immediate loading is applied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 108 publications
0
6
0
2
Order By: Relevance
“…The corticalization phenomenon, or corticalization index, is still not well explored in science. The literature reveals only a few studies that describe this phenomenon in dental/implant surgery [8][9][10]16]. Considering the presented research, this phenomenon may reflect various changes in the alveolar bone, both positive and negative, depending on multiple factors.…”
Section: Discussionmentioning
confidence: 81%
“…The corticalization phenomenon, or corticalization index, is still not well explored in science. The literature reveals only a few studies that describe this phenomenon in dental/implant surgery [8][9][10]16]. Considering the presented research, this phenomenon may reflect various changes in the alveolar bone, both positive and negative, depending on multiple factors.…”
Section: Discussionmentioning
confidence: 81%
“…The effect of this correlation may result in marginal bone loss. After five years of observation, the research showed that the higher the MBL, the greater the probability of implant loss in the smoking patients’ group, which is indirectly correlated with the occurrence of the corticalization phenomenon [ 24 , 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the types of implants, it can be stated that not only the design of the dental implant affects the corticalization phenomenon. There is a relationship between bone condition, prosthetic restoration and also the surgeon’s experience and preferences [ 24 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the fractal architecture concept is particularly interesting in surface and materials science, it also can be adapted to assess the surface of titanium dental implants. Texture analysis is used in dentistry or medicine to analyze images of computed tomography or X-ray [ 10 , 11 , 12 , 13 ]…”
Section: Introductionmentioning
confidence: 99%